Povezanost narodne in jezikovne zavesti - Mikolič, Vesna G. (Jezik in slovstvo, 2000)
The article attemps to redefine the concepts of national and language identity awarness and to analyze their mutual relationship. With its newly-gained political soveregnity and the impact processes of European integration and world-wide globalization, Slovenia has been experiencing dramatic changes in the field of ethnic identity. It is therefore pertinent to examine what the significance of national and language itentity awarness is going to be for the Slovene nation in the future.
Keywords: Slovene; slovenščina; narodne manjšine; jezikovna zavast; narodna zavest